2017
DOI: 10.32400/ja.16026.6.1.2017.45-56
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Rasio Keuangan Anggaran Pendapatan Dan Belanja Daerah (Apbd) Kota Manado Untuk Menilai Kinerja Keuangan Pemerintah Kota Manado Tahun Anggaran 2011 - 2015

Abstract: This study aims to assess the financial performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
4
0
5
Order By: Relevance
“…These findings support research findings from (Pilat & Morasa, 2017), where the condition of Manado City's financial capacity is still not ideal because the Manado City Government has not yet explored the region's potential. Another study conducted by Sulila (2019) found results that the calculation of the role of Share and Growth from the local revenue of North Gorontalo Regency was under the Quadrant II category, meaning that the share contribution to the APBD was still low.…”
Section: Discussionsupporting
confidence: 85%
“…These findings support research findings from (Pilat & Morasa, 2017), where the condition of Manado City's financial capacity is still not ideal because the Manado City Government has not yet explored the region's potential. Another study conducted by Sulila (2019) found results that the calculation of the role of Share and Growth from the local revenue of North Gorontalo Regency was under the Quadrant II category, meaning that the share contribution to the APBD was still low.…”
Section: Discussionsupporting
confidence: 85%
“…APBD ditetapkan dalam undangundang daerah, dan tahun anggaran APBD adalah satu tahun, dimulai pada tanggal 1 Januari dan berakhir pada tanggal 31 Desember. Analisis kinerja keuangan dalam APBD dilakukan dengan membandingkan hasil dari satu peri ode ke periode sebelumnya secara berurutan (Pilat & Morasa, 2017).…”
Section: Pendahuluanunclassified
“…Meanwhile, from the results of growth calculation, non-SDA regions have a higher growth value than SDA-producing regions. Pilat and Morasa (2017) examined the financial capabilities of a region, namely Manado City, using share and growth calculation methods. This study concluded that the financial capability condition of Manado City was far from ideal.…”
Section: Introductionmentioning
confidence: 99%